Pleistocene Archaeology - Migration, Technology, and Adaptation - Ono, Rintaro (Archīum Ateneo, 2020)
This book aims to review the current and latest research outcomes in the field of Pleistocene Archaeology around the world. From our understanding; the major purpose of Pleistocene Archaeology is to research deep human history of hunter-gatherers and before the development of agricultural or Neolithic societies and civilizations during the Holocene. The current geological timeline of the Pleistocene is regarded to be between about 2.58 million years ago and 11,700 years ago (Gibbard and Head 2009; Gibbard et al. 2009; Walker et al. 2018). It is then followed by the Holocene as the present geological period. In terms of human history during the Pleistocene times; a variety of human species have been existed and most important for us as modern-day Homo sapiens are the birth; evolution; and dispersal of the genus Homo during this time range. With such understanding; this book mainly focuses on archaeological studies of our species; from archaic hominins like H. erectus; H. neanderthalensis; H. floresiensis; to Homo sapiens as anatomically modern humans (AMH). The main topics of this book are: (1) human migrations in and out of Africa by Homo species; particularly by Homo sapiens who migrated into most regions of the world and various environments; (2) the development of human technology from early to archaic Homo species and Homo sapiens (e.g. stone and bone tool production and use; ornaments; rock art; hunting; fishing; gathering; resource exchange); and (3) human adaptation to new environments or environmental changes caused by past climate changes during the Pleistocene. With such perspectives in mind; this book contains a total of eight insightful and stimulating chapters related to these topics which review and discuss human history during the Pleistocene times.